Sea Turtles, their Habitats and Breeding Sites along the Syrian Coast (Latakia University Journal -Biological Sciences Series, 2024)
With the aim of studying the status of marine turtle species on the Syrian coast, and determining their habitats, reproduction, and the dangers to which they are exposed, field survey tours were conducted, during the period 2018-2021, along the Syrian coast, starting from Al-Samra area in the north to the Lebanese border in the south.Three turtle species were observed along the Syrian coast: the Green turtle (Chelonia mydas mydas), the Loggerhead turtle (Caretta caretta), and the Leatherback turtle (Dermochelys coriacea).Ten main sandy areas, where sea turtles nest and breed, were recorded. They vary in length from 1.1km (Golden Sand Beach) to 11.8km (Amrit - AL Montar Beach), with a total coast length of 50.85km. This is in addition to the small sandy stretches, of less than 1km in length, which were not recorded in this work.Several instances of sea turtle nesting have been observed: mainly the Green turtle, and to a much lesser extent the Loggerhead turtle, but not leatherback turtle at all. It was also noticed that the period of laying eggs in nests starts in mid-June and extends until late Augustt each year.Many deaths of Green and Loggerhead turtles have been observed, which are largely due to various forms of human activities on the Syrian coast.